Clinical validity of dried blood spot assay for the measurement of functional C1 inhibitor in angioedema due to C1 inhibitor deficiency - Jonathan A. Bernstein, MD; Jie Cheng, PhD; Thomas Pisani, MSc; Dan Sexton, PhD; Rachel E. Whitaker, PhD; Daniel Nova Estepan, PharmD, RPh; Neil Inhaber, MD (Journal of Allergy and Clinical Immunology: Global)
Background: Functional C1 inhibitor (fC1INH) is a key biomarker for the diagnosis of hereditary angioedema due to C1 inhibitor (C1INH) deficiency. A novel fC1INH assay from dried blood spot (DBS) reduces practical fC1INH testing limitations versus conventional fC1INH assays, but its sensitivity and specificity have not yet been characterized. Objective: We sought to assess the sensitivity and specificity of fC1INH DBS assay and conventional fC1INH ELISA and chromogenic assay. Methods: fC1INH DBS assay was performed in samples from 30 patients with previously diagnosed recurrent angioedema due to C1INH deficiency and from 100 healthy controls. Whole blood samples were spotted onto blotting paper and dried for 3 hours or longer, and then fC1INH from DBS was measured through its C1s protease inhibitory activity using liquid chromatography tandem mass spectrometry. fC1INH ELISA and chromogenic assays were performed by reanalyzing a subset of 29 patients and 50 healthy controls. Sensitivity and specificity were evaluated using a negative sample mean − 1.96 SD cutoff. Results: fC1INH DBS assay had a sensitivity of 0.93, a specificity of 0.97, and area under the curve of the receiver-operating characteristic curve of 0.996 (95% CI, 0.989-1.000). In the subset, DBS and chromogenic assay had similar sensitivity (DBS, 1.00; chromogenic assay, 0.97) and specificity (DBS, 0.94; chromogenic assay, 1.00); ELISA sensitivity was lower (0.62) and specificity similar (1.00). Conclusions: fC1INH DBS assay had similar sensitivity and specificity when contrasted with fC1INH chromogenic assay. Because of its easier sample collection and logistic benefits, fC1INH DBS assay may allow more accessible hereditary angioedema diagnostic testing, especially in underserved regions.